PRIMARY SCHOOL STUDENTS’ KNOWLEDGE on THE CONCEPT of "PLANET": A SURWEY STUDY - Kabataş Memiş, Esra; Gülünce, Merve (Social Scientific Centered Issues, 2025)
The aim of this study is to conduct a survey study on primary school students' knowledge about the concept of “planet”. The survey model was used in the study. The study was conducted in a primary school in a district with a low socioeconomic level in Istanbul. Within the scope of the study, a total of 1656 students were reached by conducting the application with 13 branches from each level. In the study, certain questions guided by the researcher were directed to the students to think and realize their drawings. They were given approximately 25-30 minutes for drawing. The drawings were evaluated using descriptive analysis method. Each drawing was analyzed separately. The concepts in the drawings were categorized as drawings related to the concepts in the solar system, drawings related to astronomy concepts, and drawings other than astronomy concepts. As a result of the coding, percentage frequency was determined according to the frequency of students' use of concepts at each level. In this context, it was determined that students in the first two levels made drawings and coding other than astronomy concepts, while students in the last two levels concentrated more on drawings and coding related to the concepts in the solar system and astronomy concepts.
Keywords: Science Education; Scientific Process Skills; concept knowledge; science education; Fen Bilgisi Eğitimi